Assessing Alternatives for Natural Gas Supply in Macedonia versus Environmental Indicators - Mladenovska D., Lazarevska A. M., Kochubovski M. (My University, 2016)
The Macedonian economy is highly energy intensive, whereby the energy sector has the greatest share in the total CO2 emissions. Namely, energy production in the country is over 70% coal-based, while there are only two gas-fired Combined Cycle Heat and Power Plants (CCHPP) which operate sporadically for a limited number of hours during winter. On the other hand, the status of the gas infrastructure, thus its availability, as well as the lack of competition on the gas market implies an almost negligible share of natural gas consumption in the residential sector. Thus, there is an urgent need to create a more competitive market to increase the natural gas consumption. The present situation in terms of natural gas supply in Macedonia is quite fragile. Gas import dependency is 100%. Moreover, the total delivered quantity originates from only one source, which implies disputable security of supply. Therefore, diversifying the natural gas supply in Macedonia shall not only strengthen energy security but it shall also contribute towards environmental protection. Due to the multifold aspects of the problem of selecting an optimal option for diversifying the natural gas supply, Multi-Criteria Decision Making (MCDM) and its techniques is recommendable. Thus, the focus in this paper is set on assessing alternatives to diversify natural gas supply in Macedonia versus the identified relevant environmental indicators, whereby Analytical Hierarchy Process (AHP) is utilized.
Keywords: natural gas, supply chain, MCDM, AHP, alternatives, assessment, environment